The discursive construction of authenticity: The case of Jeremy Corbyn. (October 2019) - Mueller, Frank; Whittle, Andrea; Gadelshina, Gyuzel
Abstract: In recent years there has been a yearning for a new, more authentic type of political leader: one who is more 'true', 'real' and 'honest'. In this paper, we analyse the discourse through which Jeremy Corbyn was framed as an 'authentic' leader in the British press during the 2015 Labour party leadership contest. We use an ethnomethodological approach to the study of media texts to investigate the methods used by journalists and commentators to establish authenticity. Our analysis uncovers three methods that were used to establish Corbyn's authenticity: consistency, atypicality and commitment to beliefs. We conclude by drawing implications from our findings for the search for authenticity in politics and society.